Tranzitusok, exitusok és modulációk: Átmenetek a Sinistra körzetben - Szirák, Péter (Studia Litteraria, 2023)
The networked narrative complexities of Bodor texts are achieved by variations and iterations, and this is especially the case with the intricately written Sinistra körzet. This allows for the kind of alinear reading that makes possible the cross-referencing of the different textual levels (e.g. a plot point, a description, or a phrase uttered by a character) as well as the self-reflexive correlation of textual elements and speech events that otherwise appear in separate contexts. This means that the text opens itself up to additional semantic possibilities and self-representational shifting. The character and landscape descriptions in Bodor often have the marked effect of blurring the lines between humans, animals, plants, and objects, thereby creating a rich field of metaphorical relations and modulations that venture into the ironic and the grotesque. Humans are substituted/reattributed as animalistic via the act of naming, in order to garner a sense of uniqueness, of the unknown, of the alien, but at the same time this substitution brings about both the annihilation and the familiarization of what is human. is paper explores the textual semiosis of Bodor texts through close readings, focusing on characterization (e.g. “vörös kakas”) and on soundscape descriptions which include the mixing of biophonic and antropophonic sounds. e narrative is “unreliable” and the speech events are idiomatic, resulting in a performative textual worlding and a grotesque-absurd modality that never quite become thetical. In Bodor, the transitions/transformations resist being allegorized.